The New Presence of China in Africa - Meine Pieter Dijk (Amsterdam University Press, 2009)
This book describes China's growing range of activities in Africa, especially in the sub-Saharan region. The three most important instruments China has at its disposal in Africa are development aid, investments and trade policy. The Chinese government, which believes the Western development aid model has failed, is looking for new forms of aid and development in Africa. China's economic success can partly be ascribed to the huge availability of cheap labour, which is primarily employed in export-oriented industries. China is looking for the required raw materials in Africa, and for new marketplaces. Investments are being made on a large scale in Africa by Chinese state-controlled firms and private companies, particularly in the oil-producing countries (Angola, Nigeria and Sudan) and countries rich in minerals (Zambia). Third, the trade policy China is conducting is analysed in China and compared with that of Europe and the United States. In case studies the specific situation in several African countries is examined. In Zambia the mining industry, construction and agriculture are described. One case study of Sudan deals with the political presence of China in Sudan and the extent to which Chinese arms suppliers contributed to the current crisis in Darfur. The possibility of Chinese diplomacy offering a solution in that conflict is discussed. The conclusion considers whether social responsibility can be expected of the Chinese government and companies and if this is desirable, and to what extent the Chinese model in Africa can act as an example - or not - for the West.
Keywords: 330; Economics; Political science; Entwicklungshilfe; Auslandsinvestition; Außenwirtschaftspolitik; China; Entwicklung; Sambia; Sudan; Subsahara-Afrika